Icon and Eucharist - Чиликов, Стоян (Sabornost - The Theological Year-book, 2012)
The paper “Icons and the Eucharist” indicates some aspects of these important and substantial dogmas of orthodox fide and actually orthodox ecclesiology. On one hand the paper gives examples of the Eucharistic and eschatological nature of orthodox icon and on the other hand illustrates the Eucharist’s eschatological character. The icon was born and developed in the Eucharistic tradition of the Church and respectively reflects the Eucharistic life, experience, upsurge and decline of the Church. The icons depict the saints praying or present them in the paradise, in Kingdom of Heaven. The Eucharist has eschatological nature and character. It occurs here and now, is a preparation for the eshaton, for the Kingdom of Heaven and the life in the future century.